The Religious Background of the Movement for Spiritual Integration into the Absolute - Melton, J. Gordon 1942- (2017)
The Movement for Spiritual Integration into the Absolute (MISA) is often portrayed as a unique and unprecedented phenomenon because of its integration of sacred eroticism into a religious worldview. This article argues that this is not the case. This integration has precedents in Taoism, Tantrism, and Western Esotericism. Several Western esoteric schools were influenced by Eastern traditions of sacred eroticism, but they also developed their own distinctive paths. While MISA primary reference for Tantrism is Tamil Nadu’s Siddha Yoga, placing the Romanian movement within a larger tradition helps both studying its doctrines and practices and avoiding frequent misunderstandings.
Keywords: MISA; Movement for Spiritual Integration into the Absolute; Sacred Eroticism; Sexual Magic; Sexuality and Western Esotericism; Tantrism